Mapping Dengue Vulnerability in West Java, Indonesia, 2019-2023 - Minsarnawati Tahangnacca; Muhamad Zidan Yusariza; Sodikin; Hasriwiani Habo Abbas (Window of Health : Jurnal Kesehatan, 2026)
Data shows that half of adults with hypertension are unaware that they have the disease, and only 21% adults with hypertension make efforts to control their blood pressure, including awareness of the disease itself, its symptoms, the need for treatment/medication, and the negative effects of the disease. Self-awareness of hypertension is necessary as an effort to control hypertension in order to avoid complications. This study aims to identify the self-awareness of adults with hypertension in the coastal area of Tarakan City. This study is a quantitative study with a cross-sectional design. The population in this study was all patients diagnosed with hypertension in Tarakan City. The sample size was 287 respondents, obtained using purposive sampling. Frequency descriptive analysis is used to analyze data. Based on the category of self-awareness of hypertension using BASIS, the majority of respondents had good awareness as shown in each category, namely 218 (76%) respondents in the category of awareness related to the disease, 248 (86.4%) respondents in the category of awareness related to symptom attributes, 270 (94.1%) respondents in the awareness category related to the need for treatment/medication, and 170 (59.2%) respondents in the awareness category related to negative impacts, as well as 250 (87%) in the total average self-awareness of hypertension. Therefore, it can be concluded that adults with hypertension in the coastal area of Tarakan City are aware of their hypertension. It is hoped that efforts to control hypertension under the supervision of doctors and other health workers will be maintained by increasing screening coverage and public awareness of hypertension through promotive, preventive, curative, and rehabilitative efforts